DE LA DIVINIDAD O DIVERSIDAD DE LAS RELIGIONES DE FRANÇOIS LA MOTHE LE VEYER - Marcelino Rodríguez Donís. (Thémata, 2008)
Resumen: En este artículo se analiza el pensamiento de La Mothe Le Veyer sobre ladivinidad desde el punto de vista del escepticismo. En realidad se trata de un análisis delas diferentes religiones de acuerdo con las ideas filosóficas del libertinismo erudito. Ladefensa de la fe Cristiana y la superioridad del Cristianismo sobre las demás religiones sebasa en las ideas de Montaigne y, sobre todo, de Charron. Hemos puesto en relación elpensamiento del autor con otros autores que han tratado este asunto desde perspectivasdiferentes.Abstract: In this article we analize the ideas of De la Mothe Le Vayer about divinity fromthe point of view of scepticism. It is, in fact, an analysis about the various religionsaccording to the philophical ideas of erudite libertinism. The defense of the Chistian faithand the superiority of Cristianity over the other religions carried about by La Mothe isbased on Montaigne´s ideas, and, above all, on Charron, s. A relationship with othersauthors, who have olso discussed the same question from different pesrspectives, isestablished.